Gratitude training to improve subjective well-being among adolescents living in orphanages - Putri Megawati; Sri Lestari; Rini Lestari (HUMANITAS: Indonesian Psychological Journal, 2019)
Adolescents who live in orphanages need to adjust to the orphanage's conditions and rules to meet their subjective well-being. The fact shows not all adolescents living in orphanages are able to achieve subjective well-being in their lives. The purpose of this study was to examine the effect of gratitude training in improving the subjective well-being of adolescents in an orphanage. A quasi-experimental design with a nonequivalent control group design was used in this study. Sixteen orphanage boys with moderately subjective well-being level participated in this study. Data were analyzed using non-parametric statistical analysis Mann Whitney u test and Wilcoxon. The results show that gratitude training is effective for improving the subjective well-being of the participants. The most improvement of subjective well-being was experienced by the participants who actively communicate with caregivers and optimistically achieve goals and expectations. The implication of this research is that to achieve subjective well-being in everyday live we should develop grateful behavior.